Tracking novel visual word learning via different methods with an original FPVS-EEG approach - Barillon, Amaury; Schiltz, Christine; Lochy, Aliette (Frontiers in Human Neuroscience, 2025)
Reading is a crucial human skill and learning novel written word forms is a life-long process. Here, we tracked the emergence of novel word lexical and neural representations after a training procedure, contrasting two learning methods, in 32 monolingual adults. Half of the novel words were provided with orthographic and phonological information (OP), and half with additional explicit semantic information (OPS). At the neural level, we demonstrate for the first time the sensitivity of EEG recordings with fast periodic visual stimulation (FPVS) to track novel visual word learning. We used an oddball paradigm, with base stimuli (pseudowords) displayed at 10 Hz with deviant stimuli (words) every fifth item (at 2 Hz), in which word-selective responses at 2 Hz demonstrate lexical discrimination. While at pre-test, novel words were not discriminated, results show clear word-selective responses over the left occipital-temporal cortex (VOTC) post-learning with both methods. This finding suggests the creation of orthographic representations for novel words and fits with current views that this region is specialized for the rapid recognition and fast learning of novel word forms. Moreover, the behavioral lexical decision data reveal significant increases in reaction times after learning, for novel words’ lexical neighbors, which suggests lexical engagement through competition arising from newly formed representation. Contrary to our expectations, no advantage was found for the OPS method. Instead, results show stronger behavioral and neural changes with the OP method. In the discussion, we highlight possible reasons for this unexpected finding. First, the current implementation of the OPS method displaying simultaneous images and words during learning could have dragged the participant’s attention away from the orthographic form. Second, the speed of presentation of stimuli might have been too fast to allow fast semantic retrieval. Finally, semantic learning might have a different timeframe than word form learning, and the current findings would reflect only the latter. Our results nevertheless highlight the rapid emergence of new word-form representations, captured by the EEG-FPVS approach.